DIGITAL COMMUNICATION AS A PRAGMATIC ENVIRONMENT - Salomova Maftuna Islomovna (International Journal of Literature and Language Studies, 2026)
The rapid advancement of information and communication technologies has significantly transformed the nature of human communication, creating new forms of interaction within digital environments. This study examines digital communication as a pragmatic environment, focusing on the realization of speech acts in email and instant messaging platforms. The research explores how technological features, communication contexts, and platform-specific conventions influence pragmatic meaning and communicative behavior. Particular attention is given to the differences between asynchronous communication, represented by email, and synchronous or semi-synchronous communication, represented by applications such as WhatsApp, Telegram, and Messenger. The study also analyzes the role of multimodal elements including emojis, stickers, GIFs, voice messages, and other digital symbols in conveying pragmatic meaning and strengthening illocutionary force. The findings indicate that digital communication has introduced new pragmatic norms and communicative strategies that differ considerably from those of traditional face-to-face interaction. While email tends to employ more formal, structured, and indirect speech acts, instant messaging platforms encourage concise, direct, and interactive communication. Furthermore, multimodal resources have become essential pragmatic markers that compensate for the absence of non-verbal cues in online communication. The study concludes that digital communication represents a dynamic and evolving pragmatic environment, making it one of the most important areas of contemporary linguistic and pragmatic research.